Is non-alcoholic steatohepatitis caused by alcohol? - Hubert E Blum (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Obesity and the associated diseases such as the metabolic syndrome, hypertryglyceridemia and diabetes mellitus type 2 are the most frequent causes of Non-Alcoholic Fatty Liver Diseases (NAFLD) [1-5]. Over time NAFLD may show mixed lobular inflammatory infiltrates and a ballooning degeneration around hepatocytes, termed Non-Alcoholic Steatohepatitis (NASH) with the potential to develop a liver cirrhosis or a Hepatocellular Carcinoma (HCC), frequently without a preexisting cirrhosis.